Thyroid replacement therapy, thyroid stimulating hormone concentrations, and long term health outcomes in patients with hypothyroidism: longitudinal study. (3rd September 2019) - Thayakaran, Rasiah; Adderley, Nicola J; Sainsbury, Christopher; Torlinska, Barbara; Boelaert, Kristien; Šumilo, Dana; Price, Malcolm; Thomas, G Neil; Toulis, Konstantinos A; Nirantharakumar, Krishnarajah
Abstract: Objective: To explore whether thyroid stimulating hormone (TSH) concentration in patients with a diagnosis of hypothyroidism is associated with increased all cause mortality and a higher risk of cardiovascular disease and fractures. Design: Retrospective cohort study. Setting: The Health Improvement Network (THIN), a database of electronic patient records from UK primary care. Participants: Adult patients with incident hypothyroidism from 1 January 1995 to 31 December 2017. Exposure: TSH concentration in patients with hypothyroidism. Main outcome measures: Ischaemic heart disease, heart failure, stroke/transient ischaemic attack, atrial fibrillation, any fractures, fragility fractures, and mortality. Longitudinal TSH measurements from diagnosis to outcomes, study end, or loss to follow-up were collected. An extended Cox proportional hazards model with TSH considered as a time varying covariate was fitted for each outcome. Results: 162 369 patients with hypothyroidism and 863 072 TSH measurements were included in the analysis. Compared with the reference TSH category (2-2.5 mIU/L), risk of ischaemic heart disease and heart failure increased at high TSH concentrations (>10 mIU/L) (hazard ratio 1.18 (95% confidence interval 1.02 to 1.38; P=0.03) and 1.42 (1.21 to 1.67; P<0.001), respectively). A protective effect for heart failure was seen at low TSH concentrations (hazard ratio 0.79 (0.64 to 0.99; P=0.04) for TSH <0.1 mIU/L and 0.76 (0.62 to 0.92; P=0.006) for 0.1-0.4 mIU/L). Increased mortality was observed in both the lowest and highest TSH categories (hazard ratio 1.18 (1.08 to 1.28; P<0.001), 1.29 (1.22 to 1.36; P<0.001), and 2.21 (2.07 to 2.36; P<0.001) for TSH <0.1 mIU/L, 4-10 mIU/L, and >10 mIU/L. An increase in the risk of fragility fractures was observed in patients in the highest TSH category (>10 mIU/L) (hazard ratio 1.15 (1.01 to 1.31; P=0.03)). Conclusions: In patients with a diagnosis of hypothyroidism, no evidence was found to suggest a clinically meaningful difference in the pattern of long term health outcomes (all cause mortality, atrial fibrillation, ischaemic heart disease, heart failure, stroke/transient ischaemic attack, fractures) when TSH concentrations were within recommended normal limits. Evidence was found for adverse health outcomes when TSH concentration is outside this range, particularly above the upper reference value.